УДОСКОНАЛЕННЯ ДЖЕРЕЛА ЖИВЛЕННЯ ДЛЯ ЗБІЛЬШЕННЯ ЕНЕРГОЕФФЕКТИВНОСТІ ІМПУЛЬСНОГО БАР’ЄРНОГО РОЗРЯДУ - Блага, О.В.; Божко, І.В.; Зозульов, В.І.; Кобильчак, В.В. (Інститут електродинаміки НАН України, Київ, 2014)
The possibility of improving pulse barrier discharge energy efficiency by including a magnetic key (nonlinear inductance) in power supply scheme was investigated; at appropriate times in discharge this magnetic key is on. It showed that as a result including a magnetic key the barrier electrical capacity discharges quickly and current of the next impulse is independent from the previous impulse, and energy capacity that remains after passing impulse on the dielectric barrier can be used productively. Improving the energy efficiency of pulse barrier discharge while connecting the magnetic key is confirmed by the example of generating ozone in such discharge. Experimentally proved, that at the same conditions in the presence of a magnetic key in the generated ozone concentration at 12 ... 50% more than that in the absence one. The most energy efficient in the generation of ozone is by the inclusion of the magnetic key at the time of about 100 ns after the start pulse barrier discharge. References 8, figures 4.